2019
DOI: 10.3389/fbioe.2019.00245
|View full text |Cite
|
Sign up to set email alerts
|

High Di-rhamnolipid Production Using Pseudomonas aeruginosa KT1115, Separation of Mono/Di-rhamnolipids, and Evaluation of Their Properties

Abstract: Rhamnolipids (RLs) are important bioproducts that are regarded as promising biosurfactant for applications in oil exploitation, cosmetics, and food industry. In this study, the newly isolated Pseudomonas aeruginosa KT1115 showed high production of di-RLs. The highest yield of RLs by P. aeruginosa KT1115, reaching 44.39 g/L after 8 days of fermentation in a 5 L bioreactor, was obtained from rapeseed oil-nitrate medium after process optimization. Furthermore, we established a new separation process that achieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…The negatively charged groups at the polar ends of RL biosurfactant molecules become protonated under these acidic conditions (Gogoi et al 2016 ). Similar results were reported by several researchers who showed that RLs activity was stable over wide ranges of temperature, salinity and pH (Abdel-Mawgoud et al 2009 ; Zhao et al 2018 ; Zhou et al 2019 ).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The negatively charged groups at the polar ends of RL biosurfactant molecules become protonated under these acidic conditions (Gogoi et al 2016 ). Similar results were reported by several researchers who showed that RLs activity was stable over wide ranges of temperature, salinity and pH (Abdel-Mawgoud et al 2009 ; Zhao et al 2018 ; Zhou et al 2019 ).…”
Section: Discussionsupporting
confidence: 90%
“…The concentration of a surfactant above which micelles or aggregates of surfactant molecule aggregates begin to develop and ST does not drop further is called the CMC. It is an essential character for evaluating the interfacial activity of surface active agents (Zhou et al 2019 ). The CMC is obtained from the intersection of the straight line passing through the plateau with the regression straight line of the linearly dependent section (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations